2021
DOI: 10.3390/biomedicines9111656
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of the Neutrophil-to-Lymphocyte Ratio, Systemic Inflammation Index, and Derived Neutrophil-to-Lymphocyte Ratio Independently Predict Invasive Mechanical Ventilation Need and Death in Critically Ill COVID-19 Patients

Abstract: Background: Hematological indices can predict disease severity, progression, and death in patients with coronavirus disease-19 (COVID-19). Objectives: To study the predictive value of the dynamic changes (first 48 h after ICU admission) of the following ratios: neutrophil-to-lymphocyte (NLR), platelet-to-lymphocyte (PLR), monocyte-to-lymphocyte (MLR), systemic inflammation index (SII), and derived neutrophil-to-lymphocyte (dNLR) for invasive mechanical ventilation (IMV) need and death in critically ill COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 41 publications
5
39
1
Order By: Relevance
“…In our cohort, demographic characteristics were similar to those of other study cohorts, non-survivors being older and having more comorbidities [ 17 , 18 ]. Regarding hematological changes induced by SARS-CoV-2, these were similar with previously reported data, with lymphopenia, neutrophilia and higher D-dimer values being associated with poor outcome [ 19 , 20 ]. The SOFA score values in COVID-19 patients admitted to ICU have important variations between studies [ 19 ], depending on: (i) the selected patients, (ii) the moment of measurement (e.g., ICU admission, before endotracheal intubation, repeated measurements), and (iii) missing data and how points were assigned [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our cohort, demographic characteristics were similar to those of other study cohorts, non-survivors being older and having more comorbidities [ 17 , 18 ]. Regarding hematological changes induced by SARS-CoV-2, these were similar with previously reported data, with lymphopenia, neutrophilia and higher D-dimer values being associated with poor outcome [ 19 , 20 ]. The SOFA score values in COVID-19 patients admitted to ICU have important variations between studies [ 19 ], depending on: (i) the selected patients, (ii) the moment of measurement (e.g., ICU admission, before endotracheal intubation, repeated measurements), and (iii) missing data and how points were assigned [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…In order to build the predictive model, after stepwise multivariate Cox PH regression was performed, the SOFA score independently predicted death together with age and NLR. Both age and NLR are considered to have independent predictive value for death [ 17 , 18 , 19 ], progression to severe or critical disease [ 19 , 30 ] and need for invasive mechanical ventilation [ 19 ] in COVID-19 patients. Moreover, given the fact that age and NLR have independent prognostic value in bacterial sepsis [ 31 , 32 ], we can speculate that this new score is reproducible in patients with COVID-19 and bacterial co-infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its predictive value for progression of severe disease [ 37 ] and mortality [ 38 ] was largely confirmed by several studies [ 39 , 40 ]. In a study carried out in an ICU [ 41 ], non-survivors had significantly lower lymphocyte values (0.99 × 10 3 /mL (±0.87) vs. 0.77 × 10 3 /mL (±0.4), p = 0.003) and higher dNLR (7.13 (±3.9) vs. 8.77 (±4.58), p = 0.002) and NLR (12.34 (±9.54) vs. 15.4 (±9.43), p = 0.001) values. Moreover, NLR and dNLR showed the best independent predictive values for invasive mechanical ventilation need and death [ 41 ].…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
“…In a study carried out in an ICU [ 41 ], non-survivors had significantly lower lymphocyte values (0.99 × 10 3 /mL (±0.87) vs. 0.77 × 10 3 /mL (±0.4), p = 0.003) and higher dNLR (7.13 (±3.9) vs. 8.77 (±4.58), p = 0.002) and NLR (12.34 (±9.54) vs. 15.4 (±9.43), p = 0.001) values. Moreover, NLR and dNLR showed the best independent predictive values for invasive mechanical ventilation need and death [ 41 ]. Data from our group [ 42 ] showed that in-hospital mortality in COVID-19 patients is predicted by a NLR > 11.38 (AUC = 0.771, p = < 0.0001, sensitivity = 77.5%, specificity = 65.9%).…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%